PEMETAAN DAERAH PENANGKAPAN POTENSIAL IKAN LAYUR (Trichiurus sp) DI PERAIRAN PANGANDARAN, JAWA BARAT - Teguh Firmansyah; Zahidah Hasan; Eddy Afrianto; Izza M Apriliani (Jurnal Airaha, 2018)
Fishing activity by catching gill nets by Pangandaran fishermen is using traditional methods inherited by ancestors especially in determining fishing ground such as seeing the color of water surface, small ripple, fish jump, the presence of foam, and see the existence of birds. Such activities make fishing activities less than optimal because the level of uncertainty is high and will impact on high operational costs such as the use of fuel wasted and trip time becomes longer. Knowledge of fishing zones is essential for fishing activities because by knowing potential fishing areas will result optimal catch and reduced effort. Information about potential fishing areas can be obtained through analysis of the distribution of a-chlorophyll in water. The research was doing from October to November 2017. The research used survey method with 7 experimental fishing activities in Pangandaran Waters. From the results of this activity can known that category distribution of fishing ground catchment area in Pangandaran spread from medium to potential category.